2018
DOI: 10.1097/pra.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Attraction Versus Action in Pedophilic Desire: The Role of Personality Traits and Childhood Experience

Abstract: Objective: Comparison of pedophilic individuals who do and do not refrain from sexually engaging with children may offer critically important information regarding the differential contributors to pedophilic attraction versus behavior. This study compared 5 traits that are potentially contributory to pedophilic attraction or behavior in both minor-attracted persons (MAPs) who refrain from sexually engaging with minors (nonacting MAPs) and those who have acted on pedophilic attractions and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…The large difference in Antisocial Personality Disorder symptoms should be vetted toward mixed results in prior research. Cohen et al (2018) studied individuals convicted of child sexual offending (n = 50), non-convicted, non-clinical individuals with pedophilic attraction (n = 195) and non-PD controls (n = 60). Their findings suggested more antisocial traits among convicted offenders, but not among non-convicted PD individuals, compared to controls.…”
Section: Impaired Cognitive Empathy and Antisocial Traitsmentioning
confidence: 99%
“…The large difference in Antisocial Personality Disorder symptoms should be vetted toward mixed results in prior research. Cohen et al (2018) studied individuals convicted of child sexual offending (n = 50), non-convicted, non-clinical individuals with pedophilic attraction (n = 195) and non-PD controls (n = 60). Their findings suggested more antisocial traits among convicted offenders, but not among non-convicted PD individuals, compared to controls.…”
Section: Impaired Cognitive Empathy and Antisocial Traitsmentioning
confidence: 99%
“…Most of what is known about CAPs are derived from offender samples, though there is likely an extensive and thus greatly understudied group of CAPs residing outside clinical- and forensic settings and who are committed to live an offense-free life (Cantor & McPhail, 2016; Cohen et al, 2018a, 2018b; Dombert et al, 2016; Levenson & Grady, 2019; Seto, 2018). For example, in an online survey among a community sample of 8718 German males, around 4% reported sexual fantasies involving prepubescent children (Dombert et al, 2016).…”
Section: Being Attracted To Children Mental Health and Online Subcult...mentioning
confidence: 99%
“…Pedophilia is a psychiatric disorder (Seto 2008), and there is evidence of brain abnormalities in those who suffer from it (Schiltz et al 2007). Impulsiveness is seen as a factor to commit sexual crimes against children, though some have argued against the idea that it has a central role; however, it is a robust finding in the literature that those who engage in sexual crimes against children suffer from grossly distorted thinking (Cohen and Galynker 2009). Moreover, research has determined that those who commit sexual crimes against children are significantly more likely to have been abused as children: a meta‐analysis by Jespersen et al (2009) has found that being a child sexual abuse victim more than triples the probability of becoming an abuser in adulthood.…”
Section: Empirical Analysismentioning
confidence: 99%